2020
DOI: 10.1186/s12891-020-3086-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MAGI2-AS3 is down-regulated in intervertebral disc degeneration and participates in the regulation of FasL expression in nucleus pulposus cells

Abstract: Background: It is known that Fas ligand (FasL) is involved in the development of intervertebral disc degeneration (IDD). A recent study reported that lncRNA MAGI2-AS3 up-regulated the expression of FasL to promote breast cancer. Therefore, we investigated the roles that lncRNA MAGI2-AS3 might play in IDD.Methods: A total of 66 IDD patients (IDD group) and 58 healthy volunteers (Control group) were recruited in this study. Quantitative real-time PCR (qRT-PCR) and western blot were used to investigate gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…ligand expression levels in NP cells (8). lncRNA PART1 has been reported to be upregulated in the central nucleus pulposus tissue of patients with IDD (17).…”
Section: Role Of Lncrna Part1 In Intervertebral Disc Degeneration Andmentioning
confidence: 97%
See 1 more Smart Citation
“…ligand expression levels in NP cells (8). lncRNA PART1 has been reported to be upregulated in the central nucleus pulposus tissue of patients with IDD (17).…”
Section: Role Of Lncrna Part1 In Intervertebral Disc Degeneration Andmentioning
confidence: 97%
“…The primary aim of clinical treatment for IDD is primarily associated with alleviating symptoms (7), though the specific mechanism of IDD pathogenesis and aetiology is not completely understood. There are three types of cells that have been reported to be involved in IDD, namely endplate chondrocytes cells, inner and outer annulus fibrosus cells and the internal nucleus pulposus (NP) cells (8)(9)(10). During IDD progression, a variety of inflammatory factors and extracellular matrix (ECM) degradation products accumulate in NP tissues, which affect NP cell physiology and function (11).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen et al [ 12 ] reported that LINC01121 act as a sponge of miR-150-5p to induced IVD progression. Cui et al [ 13 ] found that LncRNA MAGI2-AS3 is down-regulated in IVD, which was correlated with expression of FasL. LncRNA nuclear enriched abundant transcript 1 (NEAT1), a new lncRNA, has been demonstrated to serve an important role in cell apoptosis [ 14 ], non-small cell lung cancer invasion [ 15 ] and sepsis progression [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Numerous lncRNAs were shown to be deregulated in many orthopedic diseases including osteosarcoma, scoliosis, osteonecrosis of the femoral head, rheumatoid arthritis and also IDD. [20][21][22][23][24][25] For example, Cui et al 26 reported that MAGI2-AS3 was decreased in IDD and was involved in FasL expression in NP cells. Zhao et al 27 found that LINC00958 induced matrix degradation and growth via modulating miR-203/SMAD3.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous lncRNAs were shown to be deregulated in many orthopedic diseases including osteosarcoma, scoliosis, osteonecrosis of the femoral head, rheumatoid arthritis and also IDD 20–25 . For example, Cui et al 26 . reported that MAGI2‐AS3 was decreased in IDD and was involved in FasL expression in NP cells.…”
Section: Introductionmentioning
confidence: 99%